2014
DOI: 10.5588/ijtld.13.0460
|View full text |Cite
|
Sign up to set email alerts
|

Change in serum CXCL10 levels during anti-tuberculosis treatment depends on vitamin D status [Short Communication]

Abstract: Serum levels of the inflammatory C-X-C motif chemokine 10 (CXCL10) are raised in tuberculosis (TB). CXCL10 gene expression is downregulated in monocytes by metabolically active vitamin D3 (1,25dihydroxy vitamin D). Stratification of patients by serum 25hydroxyvitamin D (25[OH]D) levels at baseline showed that treatment-induced decrease in CXCL10 occurred in those with 'insufficient' and 'deficient' but not in those with 'optimal' levels. In the deficient group, 25(OH)D showed an inverse correlation with CXCL10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…5 Moreover, the increased IP-10 levels were associated with increased pathologic findings and decreased antimycobacterial activity in vitamin D 3 deficient patients. 40 Hence, the anti-inflammatory effect of vitamin D 3 may protect the host from inflammation and tissue damage during active TB disease. However, some studies reported nonbeneficial effects of vitamin D. [41][42][43] The limitation of this study is the small sample size, making minor associations difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, the increased IP-10 levels were associated with increased pathologic findings and decreased antimycobacterial activity in vitamin D 3 deficient patients. 40 Hence, the anti-inflammatory effect of vitamin D 3 may protect the host from inflammation and tissue damage during active TB disease. However, some studies reported nonbeneficial effects of vitamin D. [41][42][43] The limitation of this study is the small sample size, making minor associations difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2 [87][88][89][90][91][92][93][94][95][96], we summarized recent clinical studies on vitamin D and autophagy-adjunctive therapy for patients with pulmonary TB. As previously discussed, vitamin D treatment has diverse biological effects on host defense in TB including autophagy activation.…”
Section: Challenges Of Autophagy-adjunctive Therapeutics For Clinicalmentioning
confidence: 99%
“…Another investigation reported that vitamin D receptor agonists exert a suppression of inflammatory processes and reduce the release of CXCL10 29 . A few studies have shown an inverse relationship of serum CXCL10 and vitamin D concentrations in autoimmune diseases 29,30 that could potentially be rectified with vitamin D supplementation 31,32 . CXCL10 is also a powerful chemokine inducing Th1-mediated responses (i.e.…”
Section: Discussionmentioning
confidence: 99%